The Role of Hydrogen Sulfide on Cardiovascular Homeostasis: An Overview with Update on Immunomodulation - Pan, Li-Long; Qin, Ming; Liu, Xin-Hua; Zhu, Yi-Zhun (Frontiers in Pharmacology, 2017)
Hydrogen sulfide (H2S), the endogenous gaseous signaling molecule alongside nitric oxide and carbon monoxide, is synthesized by multiple enzymes in cardiovascular system. Similar to other gaseous signaling molecules, H2S has demonstrated a variety of biological activities, including anti-oxidative, anti-apoptotic, pro-angiogenic, vasodilating capacities and endothelial nitric oxide synthase modulating activity, and regulates a wide range of pathophysiological processes in cardiovascular disorders. However, the underlying mechanisms by which H2S mediates cardiovascular homeostasis are not fully understood. This review focuses on the recent progress on functional and mechanistic aspects of H2S in the inflammatory and immunoregulatory processes of cardiovascular disorders, importantly myocardial ischemia, heart failure, and atherosclerosis. Moreover, we highlight the challenges for developing H2S-based therapy to modulate the pathological processes in cardiovascular diseases. A better understanding of the biochemical functions of H2S might provide new therapeutic strategies for these cardiovascular diseases.